We are still the same": a study of social drama in a school carioca - Gomes, Raquel Ferreira Rangel (Faculdade de Ciências e Letras - Unesp - Araraquara., 2014)
During the fieldwork, conducted in a state school in the south zone of Rio, we used the analytical perspective of Victor Turner, from the concept of social drama. An extraordinary event broke relations governed by the standard starting drama. In crisis triggered became clear the power lines that structured social relationships within the school and this with the State Department of Education of Rio de Janeiro. The director was away, the school went through a sort of interstitial between the old rule and what was to come. The rite has become collective. Occurring public expression and symbolic reconciliation between the parties to the conflict to reconstruction, at least temporarily, the social fabric frayed. At the end prevailed code based on charisma and moral judgments. With that, the drama did not produce a break, but consolidated the traditionally existing rules that school.